IoT--Based System for Real-time Monitoring and Insect Detection in Vineyards - Stevanoska, Sintija; Davcev, Danco; Jovanovska, Elena M.; Mitreski, Kosta (ACM, 2020)
The Internet of Things (IoT) is a relatively new concept with a number of potential uses in agriculture. In this work we propose a system based on IoT for early detection of wine moth infestation, as well as monitoring the number of pests at a particular part of the season. This leads to optimization of the use of pesticides in the vineyards. The wine moths are caught using a pheromone trap with a camera attached to it. The camera is used for real-time monitoring of the trap. The output of the program is an image that indicates how many pests are currently caught on the trap. We have implemented a prototype in one of the vineyards in a Macedonian winery near Skopje City.
Keywords: Internet of Things (IoT), Real-time monitoring system, Pests, Pesticides, Image Recognition, Vineyards